Congo Basin precipitation: Assessing seasonality, regional interactions, and sources of moisture. Issue 13 (11th July 2017) - Dyer, Ellen L. E.; Jones, Dylan B. A.; Nusbaumer, Jesse; Li, Harry; Collins, Owen; Vettoretti, Guido; Noone, David
Abstract: Precipitation in the Congo Basin was examined using a version of the National Center for Atmospheric Research Community Earth System Model (CESM) with water tagging capability. Using regionally defined water tracers, or tags, the moisture contribution from different source regions to Congo Basin precipitation was investigated. We found that the Indian Ocean and evaporation from the Congo Basin were the dominant moisture sources and that the Atlantic Ocean was a comparatively small source of moisture. In both rainy seasons the southwestern Indian Ocean contributed about 21% of the moisture, while the recycling ratio for moisture from the Congo Basin was about 25%. Near the surface, a great deal of moisture is transported from the Atlantic into the Congo Basin, but much of this moisture is recirculated back over the Atlantic in the lower troposphere. Although the southwestern Indian Ocean is a major source of Indian Ocean moisture, it is not associated with the bulk of the variability in precipitation over the Congo Basin. In wet years, more of the precipitation in the Congo Basin is derived from Indian Ocean moisture, but the spatial distribution of the dominant sources is shifted, reflecting changes in the midtropospheric circulation over the Indian Ocean. During wet years there is increased transport of moisture from the equatorial and eastern Indian Ocean. Our results suggest that reliably capturing the linkages between the large‐scale circulation patterns over the Indian Ocean and the local circulation over the Congo Basin is critical for future projections of Congo Basin precipitation. Key Points: The western subtropical Indian Ocean is a dominant source of moisture to Congo Basin precipitation The recycling ratio for moisture from the Congo Basin, as simulated by CESM, is about 25% during both rainy seasons Moisture flux convergence between 800 and 600 hPa strongly influences Congo Basin precipitation seasonality